2015
DOI: 10.46989/001c.20699
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Analysis of Commercial Freshwater Fish Species Cultured in China

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is interesting to note that among morphologically distinct samples, especially dubbed as variants of flowerhorn species (Figure 2) such as Zhen Zhu, Kamfa, Parrot, Vieja, Kirin, and Thai Silk, molecular analysis classified them as one clade alongside A. trimaculatus with 0% genetic divergence, while genus with potential parentage showed > 4% divergence as in the Amphilopus genus. Previous study by Wang et al (2015) found that K2P genetic divergence among congeneric farmed freshwater fish averaged 5%, while conspecific divergence averaged 0.34%. The result is similar to this study, with intraspecific divergence is 0% and interspecific divergence being 4.95%.…”
Section: Discussionmentioning
confidence: 88%
“…It is interesting to note that among morphologically distinct samples, especially dubbed as variants of flowerhorn species (Figure 2) such as Zhen Zhu, Kamfa, Parrot, Vieja, Kirin, and Thai Silk, molecular analysis classified them as one clade alongside A. trimaculatus with 0% genetic divergence, while genus with potential parentage showed > 4% divergence as in the Amphilopus genus. Previous study by Wang et al (2015) found that K2P genetic divergence among congeneric farmed freshwater fish averaged 5%, while conspecific divergence averaged 0.34%. The result is similar to this study, with intraspecific divergence is 0% and interspecific divergence being 4.95%.…”
Section: Discussionmentioning
confidence: 88%
“…The DNeasy Tissue Kit was used to isolate DNA (Qiagen). Regarding primers for PCR, it was necessary to obtain several COI gene fragments from fish samples; therefore, we used the universal primers COIF: 5-TGTAAAAC GACGGCCAGT CCTGTGGCAATYACDCGCTGAT and COIR: 5-CAGGAAA CAGCTAT-GACNACYTCNGGRT GNCCRAAGAA (Huang et al, 2015). The following reaction conditions were used for polymerase chain reaction (PCR): 10-100 ng of DNA, 2 µl of each dNTP, 1.6 µl of each primer and 0.3 µl of Taq DNA polymerase in the given reaction buffer.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%